Concepts for a New Rapid and Simple HPLC Method for Simultaneous Determination of Metoprolol and Meldonium in Pharmaceutical Dosage Forms - Marjan Piponski; Mariana Horyn; Kristina Grncaroska; Oleksandra Oleshchuk; Elena Petrovska; Stefan Angelevski; Tetyana Uglyar; Tetyana Kucher; Liliya Logoyda (Scientia Pharmaceutica, 2022)
Simultaneous determination of the tandem of drugs, like meldonium and metoprolol, with enormous polarity differences between them, requires thorough research and careful selection of chromatographic conditions. The three different CN-cyano groups with link-based particle columns, LiChrospher CN, Waters Spherisorb CNRP, Zorbax CN SB stationary phases, were tested, in an isocratic elution system, with a running mobile phase containing various concepts of composition contents. They were first with buffering salts which included acetonitrile and ammonium phosphate in one group, and then without buffering salts but with diluted acids, composed of acetonitrile and diluted acids as the second group. We can conclude that the most optimal concepts, in terms of expressiveness and environmental friendliness, were concepts using of column Zorbax CN SB (4.6 mm i.d. × 250 mm, 5 μm) and mobile phase ACN—0.15% NH4H2PO4 (50:50 and 60:40, v/v). There are very poor available data about ideas and usable information about the development of methods for simultaneous determination of these two active substances with polarity differences between them. We suggest that our work offered detailed and successful solutions for the mentioned aim using less sophisticated equipment for quality control and a lab for routine manufacturing control.